Pseudomonas aeruginosa activates the quorum sensing LuxR response regulator through secretion of 2-aminoacetophenone. Issue 15 (23rd January 2015) - Kviatkovski, I.; Chernin, L.; Yarnitzky, T.; Frumin, I.; Sobel, N.; Helman, Y.
Abstract : Specific activation of the LuxR quorum-sensing response regulator by the volatile compound 2-aminoacetophenone, produced by the bacterium Pseudomonas aeruginosa . Abstract : In this study we identify a volatile compound produced by Pseudomonas aeruginosa, which can specifically activate the LuxR quorum-sensing response regulator of Vibrio fischeri . Comparative gas-chromatography analysis between P . aeruginosa wild type and a Δ lasR mutant strain implied that the active volatile is 2-aminoacetophenone. The use of synthetic 2-aminoacetophenone and in silico docking analyses verified the activity of the molecule and provided putative interacting residues within the binding site.